Măsuri de îmbunătăţire a şanselor tinerilor pe piaţa muncii - Fecioru, Brândușa (Calitatea Vieții, 2008)
This article contains recommendations regarding public policies aimed to increase the access of young people to the labor market. These recommendations are based on the results of research conducted during the elaboration of author’s PhD thesis. It contains aspects regarding the stimulation of entrepreneurial skills among young people, and the increase of job attendance by them.